Beyond the Veil: Colonial Legacy and the Hijab Debate in Morocco - Oumaima Bouchouk; Asmaa Bouchouk (Universitas Islam Internasional Indonesia, 2026)
The hijab has been a controversial issue in Morocco, despite the country's Muslim majority and the constitutional declaration of Islam as the state religion. This study examines contemporary debates surrounding the hijab in Morocco. It analyzes the discursive strategies of both opponents and supporters, the material implications for veiled women, and the implications of these patterns for Moroccan national identity. This article employs qualitative content analysis (QCA) and discourse analysis (DA) of Moroccan media sources, public discourse, and intellectual dialogues conducted between 2008 and 2026, arguing that the debate on the hijab is not fundamentally about women's clothing but rather a symptom of deeper, unresolved conflicts. This struggle is between colonial legacy and post-colonial identity, state secularism and popular religiosity, and competing visions of what it means to be Moroccan in the contemporary world. The analysis identifies several patterns in the opposition's discourse, such as calls for development, liberation, universal values, and feminist frameworks, as well as a strategic silence regarding the Moroccan constitution. Supporters respond with arguments based on religious obligation, individual rights, cultural authenticity, and resistance to Western hegemony. This article documents the material consequences of this debate, including professional exclusion, educational barriers, and social polarization. This article suggests that the hijab debate is likely to continue as long as Moroccan institutions operate according to secular norms that differ from the country's constitutional and religious traditions.